Accreditation and growth changes of colleges/universities with PAASCU accredited programs in Regions XI and XII - Sayson, Alicia Munez 1945- (1986)
This study sought to determine the effects of accreditation on the growth changes in seven areas of instructional concern (faculty, instruction, library, laboratories, physical plant, student services and administration) and to identify other factors working concomitantly with accreditation which have influenced growth changes in these areas as perceived by 130 full-time and part-time faculty and administrators of 8 colleges and universities accredited by the Philippine Accrediting Association of Schools, Colleges and Universities (PAASCU). Significant improvements and changes in the areas of institutional concern occurred after accreditation. Financial stability improved educational qualifications of the faculty, and improved quality of students also influenced growth. School personnel attitudes toward accreditation became more positive after they underwent the process.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Accreditation (Education).; Universities and colleges -- Accreditation. -- Philippines